PKS HELP Programme Development through Centre of Technology in Polytechnic - Saad, Khatijah Mohammed; Isa, Mazlisa Mohamed; Yurani, Fadilah; Idris, Muhammad Zaffwan (International Review of Management and Marketing, 2016)
The purpose of this paper is to provide a review on the PKS HELP as a programme developed under the Centre of Technology (COT) of Polytechnic Ibrahim Sultan through its collaboration with industries project. Final semester students diploma in graphic design and lectures of the Department of Design and Visual Communications, Polytechnic Ibrahim Sultan involved on this programme for the whole semester. The project participants will attached to SMEs under Lembaga Kemajuan Johor Tenggara (KEJORA) to help SMEs to expand and commercialise brand design and product packaging. PKS HELP consist the process of (1) consultation, (2)idea and design development and (3)R&D and innovation. The process will give exposer to students and lecturers in experiencing real industry practice and develops their professional practice. It is hoped that PKS HELP programme as presented in this paper will be beneficial to both, COT and KEJORA in promoting stronger industrial linkages this increasing national economic growth through SMEs products. Keywords: Centre of Technology, Collaboration, Design, Branding JEL Classifications: J10, M10